A facile one-pot synthesis of 8-oxo-7,8-dihydro-(2′-deoxy)adenosine in water - Chatgilialoglu, Chryssostomos (2006)
Reaction of 2-mercaptoethanol with 8-bromo-2′-deoxyadenosine and 8-bromo-adenosine in aqueous solution and in the presence of triethylamine gave the 8-oxo-adenine derivatives in very good yields. Some mechanistic details are reported.